The Effect of Differences in the Use of Flour and Plasticizers in Making Biodegradable Plastic on the Physical Characteristics of Beeswax - Yustianto, Ahmad Hadi; Sully, Diah Amara; Fauzi, Ahmad Dzakky; Amalia, Rizka (Journal of Vocational Studies on Applied Research, 2024)
Plasticis is one of the objects that is necessary in daily activities. This is because plastics makes it easier for humans to package goods. Its elastic and easy-to-use properties make plastic widely used by humans. However, on the other hand, plastic has properties that are difficult to decompose (non-degradable) so it is one of the biggest generators of waste that pollutes the environment. Biodegradable plastic or commonly called bioplastic can be an alternative product to reduce plastic waste because it is easily decomposed and more environmentally friendly. This research examines the influence of the type of starch (avocado seed flour, manga seed flour, banana peel flour, cassava peel flour) and plasticizers (glycerol, sorbitol, and polyvinyl alcohol) with beeswax additives on the characteristics of the resulting bioplastic. The best tensile strength value was found in a sample of mango seed flour, PVA type plasticizer, 0.04 gram beeswax, namely 11.35 MPa. The best elongation value was found in samples of mango seed flour, glycerol type plasticizer, 0.04 gram beeswax, namely 67%. The best percentage degradation value is bioplastic using cassava peel starch. The best swelling index value was found in samples of avocado seed flour, sorbitol type plasticizer, 0.1 gram beeswax, namely 20.16%. In terms of water content values, all samples are in accordance with SNI, namely below 20%.